External shocks, household consumption and fertility in Indonesia - Jungho Kim; Alexia Prskawetz (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2006)
This paper examines the impact of idiosyncratic income shocks on household consumption, educational expenditure and fertility in Indonesia, and assesses whether the investment in human capital of children and fertility are used to smooth household consumption. Using six different kinds of self-reported economic hardships, our findings indicate that coping mechanisms are rather efficient for Indonesian households that perceive an economic hardship. Only in case of unemployment we find a significant decrease in consumption spending and educational expenditure while fertility increases. Theses results indicate that households that perceive an unemployment shock use children as a means for smoothing consumption. Regarding the death of a household member or natural disaster we find that consumption even increases. These results are consistent with the argument that coping mechanisms even over-compensate the actual consumption loss due to an economic hardship. One important lesson from our findings is that different types of income shock may lead to different economic and demographic behavioral adjustments and therefore require specific targeted social insurance programs.
Keywords: 300; Consumption; Insurance; Fertility and Indonesia; Haushaltseinkommen; Schock; Gesamtwirtschaftlicher Konsum; Bildungsinvestition; Fertilität; Soziale Sicherheit; Indonesien